#PlasticSurgery. Issue 6 (December 2016) - Branford, Olivier A.; Kamali, Parisa; Rohrich, Rod J.; Song, David H.; Mallucci, Patrick; Liu, Daniel Z.; Lang, Dustin; Sun, Kristi; Stubican, Miran; Lin, Samuel J.
Abstract : Background: Social media use is growing inexorably, and there is public appetite for evidence-based information. Little is known about engagement by plastic surgeons with social media. The aim of this study was to examine posting about plastic surgery on Twitter, to best inform how board-certified plastic surgeons could use the hashtag #PlasticSurgery as a tool to educate patients and the public. Methods: A prospective analysis of 2880 "tweets" containing the words "plastic surgery" was performed. The following were assessed: identity of author, use of the hashtag #PlasticSurgery, subject matter, whether link to study was provided, and whether posts by surgeons were self-promotional or educational. Results: Social media posting about plastic surgery is dominated by the public, accounting for 70.6 percent of posts versus only 6.0 percent by plastic surgeons. Only 5.4 percent of all tweets contained the hashtag #PlasticSurgery, although almost half of those that did were by plastic surgeons. Of these, 61.3 percent of posts by plastic surgeons were about aesthetic surgery; additional posts were about basic science, patient safety, and reconstruction (13.9, 4.0, and 2.3 percent, respectively). Eighteen scientific articles were referenced, with a link to the Journal site posted in two tweets. Of posts by plastic surgeons, 37.0 percent were self-promotional. Conclusions: The American Society of Plastic Surgeons and its Journal have recognized that social media may be used to educate and engage. Board-certified plastic surgeons have a great opportunity to promote evidence-based plastic practice by means of #PlasticSurgery in the interests of supporting patients and the profession. Abstract : Supplemental Digital Content is available in the text.Video Discussion by Fawn Hogan, M.D., is Available Online for this Article.